ETIKA LINGKUNGAN DALAM PEMBANGUNAN BERKELANJUTAN - Moh. Solikodin Djaelani (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
Abstract Much of the world is in a treadmill situation with efforts at best simply keeping living standards from regressing and doing little to protect the environment. Often things end up m a worse state than predeveIopment The concept of sustainable development with the first use of the term in the mid -1970s was widely disseminated by the World Concentration Strategy, which sought to stimulate a more focused approach to the management of living resources and to provide policy guidance on how to do so. Sustainable development was seen as a way of shifting support for conservation and environment to make 0 also playa part in improving human welfare. Keywords: environment, sustainable development, living.